Computer simulation of composite graphene nanostructures - Бaйгaриновa Г.A.; Тогaнбaевa Л.К.; Ильин, А.К. (Recent Contributions to Physics, 2016)
In the work performed computer simulations of quantum-mechanical methods and MD studies of the energy and structural characteristics of defects in carbon nanostructures of graphene. The work presents possible computer models of graphene oxide and FLG and built a computer model of interaction between the molecules of the polymer chain with a nanostructure of graphene. During the work was used ChemOffice software (MD and quantum mechanical methods). Simulation results confirm that the graphene structure with defects may be used to substantially improve adhesion to polymers compared to the ideal structures. Results of investigations can be used to create composite materials with improved physical and mechanical properties.